Long Island enhanced aerosol event during 2018 LISTOS: Association with heatwave and marine influences. (1st February 2021) - Zhang, Jie; Mak, John; Wei, Ziran; Cao, Cong; Ninneman, Matthew; Marto, Joseph; Schwab, James J.
Abstract: The co-occurrence of enhancement in aerosol concentration, temperatures, and ozone mixing ratio was observed between June 29 and July 4, 2018 (enhanced period, EP) on Long Island (LI) and the greater NYC metropolitan area during part of the 2018 Long Island Sound Tropospheric Ozone Study (LISTOS). Two aerosol formation pathways were identified during the EP, the first being the condensation of semi- and intermediate volatility oxidation products of anthropogenic volatile organic compounds (AVOCs) under stagnant synoptic flow conditions, high temperatures and afternoon sea-breeze circulation. While this first pathway was prevalent, the most abundant organic aerosol factor was less oxidized oxygenated organic aerosol or LO-OOA. The second formation pathway occurred during a period of more persistent (synoptic) on-shore flow transporting more aged aerosol which consisted of an internal mixture of more oxidized oxygenated organic aerosol (MO-OOA), methanesulfonic acid (MSA) and sulfate. It was estimated that 35% of the sulfate observed during the mature period (an average of about 1.2 μg m −3 ) originated from oceanic dimethyl sulfide (DMS) emissions. These two formation pathways helped elucidate the sources of fine particle pollution, highlighted the interaction between human emissions and natural DMS emission, and will help our understanding of pollution affecting other urban areas adjacent to large bodies of water during hot and stagnant periods. Graphical abstract: Image 1 Highlights: Aerosol mass growth was observed and explained during a Long Island summer heatwave. Less-oxidized oxygenated organic aerosol was formed from anthropogenic sources. Aged marine influenced aerosol transported inland was internally mixed. 35% of sulfate during selected periods resulted from methanesulfonic acid (MSA).